Notes on the anthropology of the digital: challenges, opportunities from various perspectives in social research (Polis (Santiago), 2024)
In the context of my doctoral project on a digital cultural magazine, I reflect on the digitalization of social processes and social research, focusing on the challenges and opportunities faced by the Anthropology of the digital as a field, tool and object of research. The digital cultural magazine represents a space where the interaction between the online and offline worlds intertwine, offering a unique field of study to understand contemporary cultural dynamics. Digitalization has transformed the way social phenomena are researched and understood, presenting both opportunities and limitations. With these assumptions we explore theories that address multisites, points of view, intersectionality, feminist perspectives and digital ethnography, seeking to understand how the Anthropology of the digital influences social research and how we can adapt our tools and approaches to capture the richness of social processes in the digital environment.